(untitled) (Fiep Bulletin - online, 2014)
The use of differentiated content with the aim of developing the training and educating of citizens within the Physical Education classes, associated with the use of cross-cutting issues and lack of materials within the school are the challenges faced by professionals in the field of physical culture movement, thereafter comes the proposal to work with an alternative proposal but with the central goal of building values and training of the individual for social, coming from materials discarded by society and turned into toys playful world of his imagination.